2018
DOI: 10.1089/ten.tec.2017.0247
|View full text |Cite
|
Sign up to set email alerts
|

Development of In Vitro Drug-Induced Cardiotoxicity Assay by Using Three-Dimensional Cardiac Tissues Derived from Human Induced Pluripotent Stem Cells

Abstract: An in vitro drug-induced cardiotoxicity assay is a critical step in drug discovery for clinical use. The use of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) is promising for this purpose. However, single hiPSC-CMs are limited in their ability to mimic native cardiac tissue structurally and functionally, and the generation of artificial cardiac tissue using hiPSC-CMs is an ongoing challenging. We therefore developed a new method of constructing three-dimensional (3D) artificial tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 53 publications
2
66
0
Order By: Relevance
“…Several labs have deployed advanced video microscopy analyses of drug‐induced changes in contractile function of hiPSC‐CMs, from single cells to 3D tissue constructs. [ 91,98,108,114–116 ] Common mechanical readouts include changes in peak contraction/relaxation amplitudes, contraction/relaxation velocities, and beat rate (Table 2). For example, Sala et al deployed their “MUSCLEMOTION” analysis software to study the cardiotoxic agent Nifedipine (a Ca 2+ channel blocker used to treat hypertension) and learn that it reduces contraction amplitudes in single‐cell hiPSC‐CM, hiPSC‐CM monolayers, and 3D tissue constructs.…”
Section: Assays Used In Cardiotoxicity Studies To Measure Active Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Several labs have deployed advanced video microscopy analyses of drug‐induced changes in contractile function of hiPSC‐CMs, from single cells to 3D tissue constructs. [ 91,98,108,114–116 ] Common mechanical readouts include changes in peak contraction/relaxation amplitudes, contraction/relaxation velocities, and beat rate (Table 2). For example, Sala et al deployed their “MUSCLEMOTION” analysis software to study the cardiotoxic agent Nifedipine (a Ca 2+ channel blocker used to treat hypertension) and learn that it reduces contraction amplitudes in single‐cell hiPSC‐CM, hiPSC‐CM monolayers, and 3D tissue constructs.…”
Section: Assays Used In Cardiotoxicity Studies To Measure Active Forcementioning
confidence: 99%
“…[ 143 ] In the past decade, there have been several studies that have reported changes in the contractile forces produced by EHTs in response to cardiotoxic agents identified by the CiPA initiative as well as cancer drugs using micropost displacements (Table 1). [ 144–149 ] For example, Hansen et al showed that the cardiotoxic agents quinidine, chromanol, erythromycin, and doxorubicin all negatively impacted CM function using EHTs. [ 149 ] With continued improvements in EHT micropost, their use is likely to grow in drug screening assays.…”
Section: Assays Used In Cardiotoxicity Studies To Measure Active Forcementioning
confidence: 99%
“…2). Some reports have shown that cardiac constructs using iPS cells can indicate drug cytotoxicity in vitro [41], and that cardiac constructs with excessive fibrosis mimic diseased myocardium such as that seen in dilated cardiomyopathy, and can be used to analyze the pharmacological response to anti-fibrotic drugs in vitro.…”
Section: Ips Cells For Drug Screeningmentioning
confidence: 99%
“…The regenerative capacity of human pluripotent stem cells (hPSCs) can provide a virtually unlimited source of cardiomyocytes (CMs) and other functional cells for toxicology and/or tissue engineering applications (Ye et al, 2014, Chong et al, 2014, Takeda et al, 2018. Recently developed cardiac differentiation protocols now generate CM purities approaching >90% without the use of growth factors in partially-or fully-defined conditions (Lian et al, 2012.…”
Section: Introductionmentioning
confidence: 99%